Observation of the intrinsic rotation in KSTAR Ohmic L-mode plasmas. (9th February 2016) - Na, D.H.; Na, Yong-Su; Lee, S.G.; Angioni, C.; Yang, S.M.; Kim, H.-S.; Hahm, T.S.; Ko, W.H.; Jhang, H.; Lee, W.J.
Abstract: Two types of experiments were carried out to conduct an intrinsic rotation study in KSTAR. The first was a density ramp-up experiment without neutral beam injection, and the second was an experiment with beam blip technique. In these experiments, some characteristics of the intrinsic rotation were observed in the KSTAR Ohmic L-mode plasmas including: (i) a non-monotonic dependence of the core intrinsic rotation, called U-curve behaviour, with respect to the electron density and the collisionality related to the gradient of the toroidal rotation profile; and (ii) the behaviour of the anchor point in the intrinsic rotation profile for which the region exhibits a roughly flat shape and stays at nearly the same value even if the gradient of the toroidal rotation changes significantly in the core region. The location of the anchor point seems to be related to the q profile, and the toroidal rotation at the anchor point changes with the plasma operation parameters. These observations in the KSTAR Ohmic L-mode plasmas seem to be related to the rotation reversal phenomenon. A transport analysis was performed for the beam blip experiments in order to evaluate the intrinsic torque so that the U-curve behaviour can be further understood. The first results of the transport analysis in the KSTAR Ohmic L-mode plasmas show a correlation of the momentum fluxes and the intrinsic torques with the electron density and the collisionality. The rough magnitude and profiles of the intrinsic torque was experimentally obtained, and their possible mechanism is briefly discussed.